Cardiovascular and Metabolic Profile of Subjects with Acne in a Cohort of Middle-aged Patients: A General Population Study of 1,932 Subjects - Sinikumpu, Suvi-Päivikki; Jokelainen, Jari; Tasanen, Kaisa; Huilaja, Laura (Acta dermato-venereologica, 2023)
Acne vulgaris is one of the most common inflammatory skin diseases, but there are few studies of adult acne and its association with general health. The aim of this study was to examine the prevalence and clinical characteristics of adult acne at the population level among 1,932 subjects belonging to the Northern Finland Birth Cohort 1966 Study. In addition, cardiovascular and metabolic profiles of acne cases and their controls were analysed. The prevalence of adult acne was 7.9% (n = 150) with no statistical difference between the sexes. The majority of subjects presented with papulopustular acne (77.1%). Comedo acne (10.8% of all subjects) was more common in females than in males (p < 0.005). Males with acne had more abnormality in their metabolic factors than did acne-free controls; plasma glucose and insulin levels at 60 min after the 75 g glucose load were higher in males with acne than in controls (p < 0.01 for both). Corresponding associations were not seen in females. In conclusion, adult acne is common in middle-age, presenting a slightly different clinical picture in females than in males. In addition, male subjects with acne may have a higher risk of metabolic disturbances than do controls, and thus, comprehensive evaluation of patients with adult acne is needed.